2018
DOI: 10.3390/cli6020028
|View full text |Cite
|
Sign up to set email alerts
|

Land Surface Temperature Variation Due to Changes in Elevation in Northwest Vietnam

Abstract: Land surface temperature (LST) is one of the most important variables for applications relating to the physics of land surface processes. LST rapidly changes in both space and time, and knowledge of LST and its spatiotemporal variation is essential to understand the interactions between human activity and the environment. This study investigates the spatiotemporal variation of LST according to changes in elevation. The newest version (version 6) of MODIS LST data for 2015 was used. An area of 40,000 km 2 (200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 41 publications
5
30
0
Order By: Relevance
“…In contrast, the source of heat at night comes from the heat trapped during the day. Therefore, the trend during the day decreased and the trend at night increased in the highlands, with a strong correlation between nighttime and daytime patterns [69]. This information helps to better understand local warming and climate regimes, which are important in shaping agricultural production.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, the source of heat at night comes from the heat trapped during the day. Therefore, the trend during the day decreased and the trend at night increased in the highlands, with a strong correlation between nighttime and daytime patterns [69]. This information helps to better understand local warming and climate regimes, which are important in shaping agricultural production.…”
Section: Discussionmentioning
confidence: 95%
“…However, at night, the heat released by the surface is absorbed while most heat is radiated back to space by the atmosphere. In the highlands during the warm period, the trend decreased during the day and increased at night, which suggests that the warmest temperature occurred at night [69]. This variation in LST from day to night is indicative of human activities and solar characteristics during the daytime [70].…”
Section: Daytime and Night Time Change Analysismentioning
confidence: 95%
“…The annual mean LST in this region is higher than in the eastern part with the similar latitude. Taking into consideration the geographical characteristics of the area, it is observed that the low elevation increases the thermal insulation inside the basin [40]. Regarding the land cover type factor, the largest desert in China is located in this basin, which absorbs solar radiation.…”
Section: ) Correlation Analysismentioning
confidence: 99%
“…LST also increases which is directly proportional. Height increases the temperature decreases [ 37 39 ]. Built-up land plays a major role in raising the temperature [ 40 ] because of the hard concrete surface which contains almost nil water storage which leads to less humidity.…”
Section: Resultsmentioning
confidence: 99%